British Poetry from the 1950s to the 1990s
XI, 284 p.
Keywords: This collection looks at the developments in British poetry from the Movement until the present. The introduction not only provides a context for these changes but also argues that poetry criticism has been debilitated by the quest for political respectability, a trend which can only be reversed by reconsidering the idea of tradition. The essays themselves focus on general themes or individual authors. Written in a clear and informed manner, they provoke the reader into a fresh awareness of the nature of poetry and its relation to society.